FIRE DISASTER MODEL FOR CAMPUS BUILDING, A CASE STUDY OF BRAWIJAYA UNIVERSITY - Heru Sufianto; Agung Murti Nugroho; Satya Aditama (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2017)
ABTSRACTFires in buildings have significant impact on communities both socially and economically. In education facilities, fire incidents have potential impact on academical activities and research products. Fire authorities, practitioners and relevant bodies have been addressed this issue partially on the points of physical aspects and management addressed to fire safety. This study seeks the importance element of a framework that should be implemented comprehensively increasing campus building fire protection around the clock. Number of buildings in University of Brawijaya were used as the sample study. Assessment on fire protection tools of buildings have been performed to seek potential fire risk, a questionnaire has been dirtributed online throughout building occupants seeking level of awareness and knowledge toward fire incidents. Meanwhile, existing fire disaster models implemented in some campus buildings been reviewed. The study found 4 elements of the fire disaster model to be taken into account, including: occupant’s knowledge and awareness, quality infrastructure of the building, insentives, and control.Keywords: fire safety management, fire protection, building occupants, fire safety awareness.